2010
DOI: 10.1093/eurheartj/ehq059
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in incidence and fatality of out-of-hospital cardiac arrest in females of the reproductive age

Abstract: Reproductive females had a lower incidence and a better outcome of OHCA than females of other ages and males, which might be explained by cardioprotective effects of endogenous oestrogen on OHCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 34 publications
10
80
4
1
Order By: Relevance
“…43 Women, on the other hand, are more likely to survive during reproductive years. 8,23,26,30 This advantage disappears in a linear fashion as they age. 10,11 Women have increased chest wall compliance and disparities in pharmacobiology, making it easier to resuscitate them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Women, on the other hand, are more likely to survive during reproductive years. 8,23,26,30 This advantage disappears in a linear fashion as they age. 10,11 Women have increased chest wall compliance and disparities in pharmacobiology, making it easier to resuscitate them.…”
Section: Discussionmentioning
confidence: 99%
“…Four show a survival advantage in younger women. 8,23,26,30 However, the same interaction has not been tested across the age spectrum for men.…”
Section: Academic Emergency Medicinementioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Kitamura and his group has demonstrated that women aged 13-49 years had a significantly lower incidence and a better outcome after OHCA compared to men in the same age cohort. 9 Topjian et al, 8 who studied in-hospital cardiac arrest has shown that women of child-bearing age (15-44 years of age) were more likely to survive to hospital discharge than men. 8 Both groups have speculated that this difference might be explained by potential cardioprotective effects of female sex hormones 8,9 and our results lend further support to that speculation.…”
Section: Discussionmentioning
confidence: 99%
“…9 Topjian et al, 8 who studied in-hospital cardiac arrest has shown that women of child-bearing age (15-44 years of age) were more likely to survive to hospital discharge than men. 8 Both groups have speculated that this difference might be explained by potential cardioprotective effects of female sex hormones 8,9 and our results lend further support to that speculation. Although the epidemiology and outcomes from OHCA and inhospital cardiac arrest differ, improved survival outcomes for women in the child-bearing age group is a consistent finding across the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation